2010
DOI: 10.1155/2010/301395
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Emission Effects on Aerosol‐Cloud Interactions: Insights from Two Case Studies

Abstract: Two case studies are discussed that evaluate the effect of ocean emissions on aerosol-cloud interactions. A review of the first case study from the eastern Pacific Ocean shows that simultaneous aircraft and space-borne observations are valuable in detecting links between ocean biota emissions and marine aerosols, but that the effect of the former on cloud microphysics is less clear owing to interference from background anthropogenic pollution and the difficulty with field experiments in obtaining a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 97 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…During the same cruise, high CCN activity has been documented by Mochida et al []. Earlier studies also documented an enhanced CCN activity over the open ocean waters during high biological activity [ Korhonen et al , ; Meskhidze and Nenes, , ; Sorooshian et al , ; Sorooshian and Duong , ; Vallina et al , ]. Although we do not have the size distribution data of diacids in the present cruise, previous study has shown that the size‐segregated molecular distribution of oxalic acid and other low molecular weight diacids are enriched in the fine mode particles [ Miyazaki et al , ].…”
Section: Resultsmentioning
confidence: 47%
“…During the same cruise, high CCN activity has been documented by Mochida et al []. Earlier studies also documented an enhanced CCN activity over the open ocean waters during high biological activity [ Korhonen et al , ; Meskhidze and Nenes, , ; Sorooshian et al , ; Sorooshian and Duong , ; Vallina et al , ]. Although we do not have the size distribution data of diacids in the present cruise, previous study has shown that the size‐segregated molecular distribution of oxalic acid and other low molecular weight diacids are enriched in the fine mode particles [ Miyazaki et al , ].…”
Section: Resultsmentioning
confidence: 47%
“…The NWP, NAT, and CAT regions are oceanic regions located downwind of the major dust and industrial pollution sources. Thus, these oceanic regions are substantially influenced by the mixture of ocean emissions, the ship exhaust, and the transported continental emissions (Sorooshian and Duong, 2010). It is apparent the CALIOP assimilation over the maritime downwind regime has the most efficient improvements among the four regimes.…”
Section: Comparison Of the Analysis With Caliopmentioning
confidence: 99%
“…The emissions from oceans could mix with ship and continental emissions and form a complicated mixture of marine aerosol particles. Thus, the sources and properties of marine aerosols can be affected by ocean emissions, ship exhaust, and transported continental emissions [ Sorooshian and Duong , ]. Here we choose three oceanic regions, and their seasonal vertical profiles of aerosol extinction are shown in Figure .…”
Section: Seasonal Variation Of the Vertical Distribution Of Aerosol Pmentioning
confidence: 99%